(untitled) (Communications in Computational Physics, 2009)
Recently Hari Shroff and his collaborators [Nano Letters 5 (2005)] developed a nanoscopic force sensor, but the force which they measured in their single molecular experiment was much lower than the theoretical critical value. In order to fix this problem, we investigate the micromechanics of dsDNA based on the worm-like chain model and flexible hinge model by using Monte Carlo algorithm. The simulation results not only address Hari Shroff's experiment difficulty reasonably, but also provide strong support for flexible hinge mechanism put forward recently by Yan and Marko [Phys. Rev. Lett. 93 (2004)].